2002
DOI: 10.1093/treephys/22.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Variation in specific needle area of old-growth Douglas-fir in relation to needle age, within-crown position and epicormic shoot production

Abstract: Variation in specific needle area (SNA; cm2 projected fresh needle area g-1 oven-dried needle weight) was investigated in relation to needle age, within-crown position and epicormic shoot production in 450-year-old Douglas-fir (Pseudotsuga menziesii Mirb. (Franco) var. menziesii) trees. Specific needle area decreased with increasing needle age. The magnitude and rate of change in SNA with needle age were greatest for lower-crown branches, and decreased toward the middle- and upper-crown branches. For all branc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
2

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 43 publications
5
23
2
Order By: Relevance
“…In this case, SLA of a given foliage age class declined with increasing distance from bole. Although we could not test this trend for Douglas-fir in our study, Ishii et al [17] found a similar decline in SLA with increasing distance from bole in Douglas-fir old growth, particularly in the upper portion of the crown. The greater SLA of foliage close to the bole most likely is a direct result of the light environment at the time of needle development, and perhaps secondarily a response to gradients in water potential from branch base to tip.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…In this case, SLA of a given foliage age class declined with increasing distance from bole. Although we could not test this trend for Douglas-fir in our study, Ishii et al [17] found a similar decline in SLA with increasing distance from bole in Douglas-fir old growth, particularly in the upper portion of the crown. The greater SLA of foliage close to the bole most likely is a direct result of the light environment at the time of needle development, and perhaps secondarily a response to gradients in water potential from branch base to tip.…”
Section: Discussioncontrasting
confidence: 81%
“…Other tree-and stand-level factors, including leaf area index, had little influence on SLA after accounting for these covariates. In other studies, foliage age class [2,7,13,17] and branch location [21,30] have consistently been key factors controlling SLA. The data collected from hybrid spruce provided a unique opportunity to test the effect of distance from bole on SLA within a branch.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…In Douglas-fir, LMA increases with irradiance during the first growing season (Aussenac 1973;Warren et al 2003b), and then increases with needle age regardless of light in subsequent years (Ishii et al 2002;this study) In both cases, the increase in LMA is modulated through changes in both needle thickness and tissue density, although in developing needles the changes mostly take place in the palisade mesophyll layer (Aussenac 1973), whereas in ageing needles, they are more likely to occur in the hypodermal layer and other lignified tissues (Apple et al 2002). According to Niinemets et al (2005Niinemets et al ( , 2006 who discussed the possible effect of light acclimation versus leaf ageing on LMA and g i in Mediterranean broadleaf evergreens, the initial positive effect of light on LMA and g i (area basis) is a consequence of the greater chloroplast to total leaf surface area ratio of the 'sun leaf type' palisade tissue (see references given therein), whereas the subsequent negative effect of LMA on g i (mass or area basis) reflects the accumulation of cell wall compounds which would impede the diffusion of CO 2 in the liquid phase.…”
Section: Age-related Decline Of G I Versus Lma and Light Acclimationmentioning
confidence: 99%